(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
This article analyzes the role of the Republic of Uzbekistan in the global biodiversity conservation strategy, its obligations under international environmental conventions, and the practical measures currently being implemented. The study provides a scientific basis for the country’s contribution to ensuring ecosystem stability in Central Asia, specifically focusing on the unique mountain landscapes of the Kashkadarya region and the global significance of afforestation projects on the desiccated bed of the Aral Sea. Using statistical data, the article illustrates the population dynamics of rare and endangered flora and fauna, the expansion of the Protected Natural Areas (PNA) network, and national initiatives against climate change. Furthermore, scientific recommendations are proposed for the implementation of digital monitoring systems and the development of transboundary ecological corridors to enhance biodiversity preservation.